Master’s thesis in software engineering – object, subject, contents of research - Sydorov, M.O. (PROBLEMS IN PROGRAMMING, 2022)
Nowadays scientific researches In Ukraine are based on formulating the goals of research, us- ing the concept of object and subject of research. Moreover, as time has shown, this is an important stage of work on which the eﬀectiveness of the study depends. Both the total use of a software in diﬀerent arias of life and improvement of software engineering prepare better conditions for this stage of the dissertation research. Modern software engineering uses scientific research methods that should be used to perform dissertation research. The purpose of this article is the following: to provide recommendations for the formulation of the object and subject of the master’s thesis. Special phocus is made on specialization in the software engineering fundamentals. It also aimed at describing the scientific methods of evidence-based research in the master’s thesis. It pays attention to the results presentation. These points are considered in the context of the conditions that have developed in education and the relevant problems that have arisen in the Universities′ curriculum. There are some problems in choosing the topics of master′s thesis. The one is objective in nature and arises from the combination of the domain of software engineering with application domains in a context of specialization. The article is aimed at masters in software engineering and their supervisors.Prombles in programming 2022; 2: 22-36